Urbanization Trend: Viewed from Socioeconomic Status, Regional Minimum Wage, Employment, and Urbanization Rate Factors - Setiawan, Rizky Bintang (FONDATIA, 2025)
This study aims to reveal the urbanization trend for Vocational High School (VHS)graduates which is influenced by socioeconomic status, minimum wage level, and employment. This study uses a quantitative methodology and is structured as an explanatory study. The study involved 478 samples of VHS alumni working in big cities by purposive random sampling. Data was collected through a questionnaire instrument using an online form which was declared content valid using Aiken with a range of 0.81 to 0.94 and constructively using Exploratory Factor Analysis (EFA) with a Keyser Mayer Olkin (KMO) value between 0.598 to 0.765. The instrument has also shown a reliability coefficient of 0.789 to 0.867 which means the instrument is reliable. Analysis was conducted via Structural Equation Modeling (SEM) with LISREL. The findings of this study indicate that (1) socioeconomic status, minimum wage level, and employment exert a positive and significant influence on the urbanization rate of VHS graduates by 35.1%; (2) Socioeconomic status and minimum wage levels positively and significantly affect on employment by 20.8%; (3) Socioeconomic status and minimum wage rates through employment positively and significantly affect on the urbanization rate of VHS graduates of 68.7%.